2017
DOI: 10.1111/jgs.15026
|View full text |Cite
|
Sign up to set email alerts
|

Discharge Plans for Geriatric Inpatients with Delirium: A Plan to Stop Antipsychotics?

Abstract: In our health system, the majority of geriatric patients with delirium, discharged on a new antipsychotic had no instructions outlined to outpatient providers for discontinuation management. Further interventions could target increasing antipsychotic guidance at transitions of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 21 publications
3
16
0
Order By: Relevance
“…Approximately one third of patients in this study were discharged on an antipsychotic. Other findings from this study align with prior research 9 in that there was a positive association between antipsychotic discharge instructions for continuation or discontinuation and specialty consult recommendations.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Approximately one third of patients in this study were discharged on an antipsychotic. Other findings from this study align with prior research 9 in that there was a positive association between antipsychotic discharge instructions for continuation or discontinuation and specialty consult recommendations.…”
Section: Discussionsupporting
confidence: 88%
“…Compared to previous studies, 5,9 patients included in this retrospective review were more likely to be discharged on an antipsychotic that was initiated during admission for management of delirium. Approximately one third of patients in this study were discharged on an antipsychotic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 In addition, a systematic review and metaanalysis of 19 studies found no benefi t of antipsychotic medications for preventing or treating delirium in hospitalized adults. 29 Antipsychotics are often continued indefi nitely A retrospective chart review at a US academic health system found 30 that among 487 patients with a new antipsychotic medication prescribed during hospitalization, 147 (30.2%) were discharged on an antipsychotic. Of these, 121 (82.3%) had a diagnosis of delirium.…”
Section: Antipsychotics May Worsen Deliriummentioning
confidence: 99%
“…Antipsychotics have been identi ed as being overused and having limited clinical bene t for BPSD [6,7] and should not be continued for more than three months [8]. Consequently, the risk for PWD remains high if these medications are not discontinued at discharge [9]. The prevalence of PIMs for PWD in the community has been reported in a systematic review, to range from 10-56% and is higher in nursing home settings [5].…”
Section: Introductionmentioning
confidence: 99%